Biomechanical study of two different fixation methods for the treatment of Neer III proximal humerus fractures - Bangjun Cheng; Xiping Jiang; Xiaofeng Zhang; Shixin Guo; Qi Chen; Shengchao Du; Yi Luo; Yaohua He (BMC Musculoskeletal Disorders)
Abstract Background The lateral locking plate for the proximal humerus is currently the most commonly used surgical procedure for the treatment of elderly proximal humeral comminuted fractures. Previous studies have found that the rate of postoperative complications in patients of proximal humerus fractures with medial column involvement is relatively high. Through biomechanical methods, this study aims to investigate the effectiveness of the conventional lateral locking plate fixation along with the addition of the metacarpal supporting plate on the medial column in the treatment for proximal humeral fractures involving the medial column. The goal is to reduce the rate of postoperative internal fixation failure in patients with medial column injury. Methods Thirty artificial synthetic humerus models are used as experimental samples. A proximal humerus fracture model with medial column injury was created, and then divided into two groups. Group A was fixed with a proximal humerus lateral locking plate (single-plate group). Group B was fixed with a proximal humerus lateral locking plate and a metacarpal supporting plate on the medial column (double-plate group). The failure displacement, stiffness, and strength of the repaired proximal humerus fractures with two different methods were tested under compression at posterior extension of 15°, forward flexion of 15°, and vertical direction. Results There was no statistical significance in the comparison of the failure displacement of repaired proximal humeral fractures between the two groups under compression at posterior extension of 15° and forward flexion of 15° (P > 0.05). However, the failure displacement of the fracture was longer in single-plate group than in double-plate group under compression at vertical direction (P < 0.05). The double-plate group was better in terms of biomechanical stiffness and strength compared to the single-plate group at all three testing angles (P < 0.05). Conclusions For patients whose proximal humeral fractures involve the medial column, the addition of a support plate on the medial side of the humerus is recommended along with the lateral locking plate. The double-plate strategy can increase the stability of the medial column of the proximal humerus, and enhance the overall biomechanical property of the repaired proximal humerus.